Model of polarization selectivity of the intermediate filament optical channels - Khmelinskii, Igor (2018)
Recently we have analyzed light transmission and spectral selectivity by optical channels in Muller cells and other transparent cells, proposing a model of their structure, formed by specialized intermediate filaments [1,2]. Our model represents each optical channel by an axially symmetric tube with conductive walls. Presently, we analyze the planar polarization selectivity in long nanostructures, using the previously developed approach extended to structures of the elliptic cross-section. We find that the output light polarization degree depends on the a/b ratio, with a and b the semiaxes of the ellipse. Experimental tests used a Cr nano-strip device to evaluate the transmitted light polarization. The model adapted to the experimental geometry provided an accurate fit of the experimental results. Published by Elsevier B.V.